2022
DOI: 10.3390/ijerph192214733
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Work, Leukemia, and Cancer Risk: A Systematic Review and Meta-Analysis

Abstract: Background: With the development of the semiconductor industry over the past 60 years, various occupational diseases have been reported to coincide with rapid industrial growth. Among these occupational diseases, the association between semiconductor work and cancers, including leukemia, remains controversial. Therefore, this systematic review and meta-analysis assesses the associations between semiconductor work, leukemia, and cancer risk. Methods: The core research databases, including PubMed, were screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This issue is reflected in the role of clinicians who need to have multilevel competences. Finally, it should be noted that novel materials, among which semiconductors, appear to be safe for workers and are not clearly associated with a specific risk of cancer development [ 292 , 293 , 294 ]; however, adequate control exposure and monitoring programs should be applied by global agencies.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is reflected in the role of clinicians who need to have multilevel competences. Finally, it should be noted that novel materials, among which semiconductors, appear to be safe for workers and are not clearly associated with a specific risk of cancer development [ 292 , 293 , 294 ]; however, adequate control exposure and monitoring programs should be applied by global agencies.…”
Section: Discussionmentioning
confidence: 99%
“…Over several decades, the potential hazards of the semiconductor industry have increased, but epidemiological studies have reported no significant excess cancer incidence or mortality among semiconductor workers in the United Kingdom (UK), the United States (US), Taiwan, and South Korea [ 12 – 16 ]. A systematic review and meta-analysis also reported no significant association between semiconductor work and leukemia [ 17 ].…”
Section: Introductionmentioning
confidence: 99%